Linguopragmatic functions of the icon, index, and symbol system in euphemistic discourse - Matyakubov, Zohid Muminbaevich (The Lingua Spectrum, 2026)
This article examines the linguopragmatic functions of icon, index, and symbol in euphemistic discourse based on Charles Sanders Peirce’s semiotic theory. The study explores how euphemistic expressions perform semantic mitigation, concealment of reality, and ideological transformation within totalitarian discourse. An interdisciplinary approach combining semiotics, pragmatics, discourse analysis, and critical linguistic theory is employed. George Orwell’s novel “1984” serves as the primary source for analysis because of its representation of manipulative political language and ideological communication. Euphemistic units such as “Big Brother,” “Ministry of Love,” “Ministry of Peace,” “Joycamp,” “vaporized,” and “unperson” are analyzed through the categories of icon, index, and symbol. The findings reveal that euphemisms function not only as stylistic devices but also as ideological tools shaping public consciousness and controlling perception. The study demonstrates that the interaction of semiotic signs creates a linguopragmatic mechanism reinforcing ideological domination and cognitive control in political discourse and contemporary authoritarian communication practices within modern state propaganda systems.